2021
DOI: 10.1088/1757-899x/1009/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between aluminum alloys behavior in incremental sheet metal forming process of frustum pyramid shaped parts

Abstract: Single point incremental forming is a new emerging technology, used mainly for prototype development or small series production, with good prospects in industrial implementation. However, the parts manufactured through this process often presents low accuracy, thus the industrial implementation is yet limited. Incremental forming process can be done with the help of different technological equipment, such as industrial robots and numerically controlled machines. Since the process is still in development phase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…They found that forming sheets incrementally with ultrasonic assistance can reduce the springback effect. Rusu et al [146] studied the behaviour of the following various aluminium alloys: AA 2007, EN AW 5754 and EN AW 6060 that were formed using SPIF, examining forming forces, thickness distribution and springback. The largest springback effect was seen in the AA 2007 alloy, which was accompanied by the lowest accuracy.…”
Section: Springback Reductionmentioning
confidence: 99%
“…They found that forming sheets incrementally with ultrasonic assistance can reduce the springback effect. Rusu et al [146] studied the behaviour of the following various aluminium alloys: AA 2007, EN AW 5754 and EN AW 6060 that were formed using SPIF, examining forming forces, thickness distribution and springback. The largest springback effect was seen in the AA 2007 alloy, which was accompanied by the lowest accuracy.…”
Section: Springback Reductionmentioning
confidence: 99%
“…With the use of the same equipment, due to the great flexibility of the process, there are many manufacturing possibilities of the different shapes and sizes of parts. However, the complexity of the geometric shapes that can be formed depends on many process parameters [10][11][12], such sheet thickness, forming angle, tool size, step size, punch toolpath or the available power of the technical equipment.…”
Section: Fig 1 Spif Process Principlementioning
confidence: 99%
“…The springback was found to increase with increasing tool diameter. Rusu et al (2021) studied the behaviour of different EN AW-2007, EN AW-5754 and EN AW-6060 aluminium alloy sheets deformed through SPIF regarding springback effect. Frustum pyramids made of EN AW-2007 alloy presented the highest springback.…”
Section: Introductionmentioning
confidence: 99%